Streptomyces sp. JCK-6131 Protects Plants Against Bacterial and Fungal Diseases via Two Mechanisms - Le, Khanh Duy; Kim, Jeun; Nguyen, Hoa Thi; Yu, Nan Hee; Park, Ae Ran; Lee, Chul Won; Kim, Jin-Cheol (Frontiers in Plant Science, 2021)
Plant bacterial and fungal diseases cause significant agricultural losses and need to be controlled. Beneficial bacteria are promising candidates for controlling these diseases. In this study, Streptomyces sp. JCK-6131 exhibited broad-spectrum antagonistic activity against various phytopathogenic bacteria and fungi. In vitro assays showed that the fermentation filtrate of JCK-6131 inhibited the growth of bacteria and fungi with minimum concentration inhibitory (MIC) values of 0.31–10% and 0.31–1.25%, respectively. In the in vivo experiments, treatment with JCK-6131 effectively suppressed the development of apple fire blight, tomato bacterial wilt, and cucumber Fusarium wilt in a dose-dependent manner. RP-HPLC and ESI-MS/MS analyses indicated that JCK-6131 can produce several antimicrobial compounds, three of which were identified as streptothricin E acid, streptothricin D, and 12-carbamoyl streptothricin D. In addition, the disease control efficacy of the foliar application of JCK-6131 against tomato bacterial wilt was similar to that of the soil drench application, indicating that JCK-6131 could enhance defense resistance in plants. Molecular studies on tomato plants showed that JCK-6131 treatment induced the expression of the pathogenesis-related (PR) genes PR1, PR3, PR5, and PR12, suggesting the simultaneous activation of the salicylate (SA) and jasmonate (JA) signaling pathways. The transcription levels of PR genes increased earlier and were higher in treated plants than in untreated plants following Ralstonia solanacearum infection. These results indicate that Streptomyces sp. JCK-6131 can effectively control various plant bacterial and fungal diseases via two distinct mechanisms.